Systematics, taxonomy, and distribution of species of Myriogenospora G.F. Atk. (Clavicipitaceae, Hypocreales, Ascomycota) - Cruz Laufer, Armando J. (2019)
Based on new specimens of Myriogenospora spp. from Costa Rica and Panama, we present morphological analyses, systematic conclusions, additions to host ranges, and geographical distribution data for the two species currently classified in this genus. Myriogenospora atramentosa (Berk. & M.A. Curtis) Diehl differs from Myriogenospora linearis (Rehm) J.F. White & Glenn in the ascus and part-spore morphology, a different position in the molecular phylogeny, and the host range. We conclude that the two species are not congeneric and propose that M. linearis should be called Balansia linearis (Rehm) Diehl.